Measurement of thyroid hormones and cortisol in horses with an automated immunoassay analyzer - Suárez-Esquivel, Marcela (2016)
Even though thyroid gland diseases are unusual in horses, it is important to have a reference interval for thyroid hormones in this species at every veterinary endocrine laboratory. In addition, cortisol and thyroid hormone measurement is useful in horses, not only for disease diagnosis, but as a tool for monitoring and researching performance and metabolic rate.The objectives of this study included (i) to test the capacity of the automated analyzer AIA 360® (TOSOH Bioscience) to measure thyroid hormones and cortisol in equine serum in a reliable way, and (ii) to establish a reference interval for thyroid hormones in Costa Rican horses using the AIA-360®.A total of 68 healthy and treatment free horses (31 males and 37 females) were sampled. Horses were grouped into three different categories according to their ages. Serum concentrations of total thyroxine (TT4), free thyroxine (FT4), and cortisol were quantified with the AIA-360®. Statistic relationships of hormonal values, gender and age were determined using Kruskal-Wallis, Dunn and Wilcoxon (U Man-Whitney) tests. P <0.05 was considered significant.Selected reference intervals were: TT4 14.16 – 46.33 nmol/L, FT4 3.60 – 16.09 pmol/L and cortisol 23.45 – 166.64 nmol/L. No statistically significant relationship was found between gender, age, and hormone values. Besides, significant relationships (p<0.05) were found between hormone levels and some environmental parameters. Animals living at higher altitudes showed higher cortisol levels, while cortisol decreases as the environmental temperature rises. Moreover, the FT4 levels are higher as precipitation increases. Finally, TT4 seems to be lower as day light length increases; however, no statistical relationship was found (p<0.30).  Our results show that the use of the automated analyzer AIA-360® is suitable to measure thyroid hormones and cortisol, and that the values found are comparable with other studies and analysis techniques.